2021
DOI: 10.21787/jbp.13.2021.369-381
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Rural Development on Poverty Gap, Poverty Severity and Local Economic Growth in Indonesia

Abstract: The effect of rural development in reducing the poverty gap and economic growth has not been much analyzed in recent studies. This study examines the effects of rural development (as calculated by using the Village Development Index, VDI) on poverty and economic growth. Precisely, poverty is measured by the depth of poverty (as measured by Poverty Gap Index, P1) and poverty severity (as measured by Poverty Severity Index, P2) using the aggregate data at the district level in Indonesia. Understandably, many fac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 27 publications
0
13
0
2
Order By: Relevance
“…This increase could be used more for economic recovery, which still requires a lot of financial support through the Village BLT program, or maybe it can also be used to increase infrastructure development because most of these areas are located in the eastern part of Indonesia, which still lags behind other regions. Increasing the development of rural areas, especially in disadvantaged areas, must be accelerated to reduce the depth and severity of poverty in the region (Handoyo et al, 2021).…”
Section: Resultsmentioning
confidence: 99%
“…This increase could be used more for economic recovery, which still requires a lot of financial support through the Village BLT program, or maybe it can also be used to increase infrastructure development because most of these areas are located in the eastern part of Indonesia, which still lags behind other regions. Increasing the development of rural areas, especially in disadvantaged areas, must be accelerated to reduce the depth and severity of poverty in the region (Handoyo et al, 2021).…”
Section: Resultsmentioning
confidence: 99%
“…So, Pangkalpinang City Government needs to conduct a study to increase the contribution of Regional Revenue to the Regional Budget. Research results (Handoyo et al, 2021) found that regions with higher self-reliance will find it easier to overcome and reduce poverty levels. Therefore, the Pangkal Pinang City Government needs to increase its independence in financing the Regional Budget because it has a broad impact (Tan, 2020).…”
Section: Introductionmentioning
confidence: 95%
“…This finding follows Kakwani and Son (2003), who state that poverty reduction can be achieved by increasing economic activity. It is more due to increasing the involvement of the poor in economic act (Handoyo et al, 2021).…”
Section: B the Nexus Between Village Funds And Other Variables Toward...mentioning
confidence: 99%